MANIFESTASI PRINSIP KESANTUNAN, PRINSIP KERJA SAMA, DAN IMPLIKATUR PERCAKAPAN PADA INTERAKSI DI LINGKUNGAN SEKOLAH - Eko Kuntarto; Abdoel Gafar (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
The language has many functions, in ataranya as a means of self expression, communication tools, a tool of social control, and the interaction. The study of language tend to concentrate on its function as a tool for suffixed interaction cannot be released from the wearer, that is, the community. The school as a place of teaching language in fact is social language usage areas (societal domain) which has its own livery.This study examines the use of spoken language in the Association in the Group-anschool between students, teachers, and employees. The research focus is on a range of spoken language that has the meaning depends on context (contex depending).As for the linguistic aspects are examined is the manifestation of the principle of politeness, the principle of cooperation, interaction and conversation on the implikaturat school.This research uses qualitative design. The techniques used in data collection is the technique check out-Libat Ably (SLC), divariasi with the note field.The results of this study are: (1) Politeness can be manifested in the kind of acts representative said, expressive, komisif, and directive, (2) the principle of Politeness and the principle of cooperation can be manifested in implikatur conversation; (3) On the official topic of conversation with the situation, politeness is manifested with pematuhan on the principle of cooperation and the use of implikatur; (4) On the situation of the conversation with the topic is not official, the principle of cooperation (PK) take precedence over the principle of politeness (PS); (5) on the conversation between student-teacher, a distance of so-bad luck and social status is no longer a major consideration to convey a polite speech.Based on the research results presented recommendations to make politeness became one of material in language learning at school.Keywords: politeness principles, principles of cooperation, implikatur conversation